PENGARUH CITY BRANDING TERHADAP KEPUTUSAN KUNJUNGAN KEMBALI (Studi Pada Wisatawan Kampung Coklat ) - NINGSIH, AINI NURFITA (Jurnal Ilmiah Mahasiswa FEB, 2018)
This study aims to analyze the influence of city branding on revisit decision to Kampung Coklat. The population and sample used in this study are 160 visitors of Kampung Coklat. The sampling technique used in this study is purposive sampling. The data of this study are primary data obtained from 160 returned Likert-scale questionnaires, which were analyzed using multiple linear regression analysis in SPSS version 19. The independent variable of this study is city branding (X) consisting of presence, place, potential, pulse, people and pre-requisites, while the dependent variable is revisit decision (Y). The result of this research, based on data analysis and hypothesis testing, is that city branding (X) simultaneously and partially have a significant effect on revisit decision (Y). In addition, the variable of place has also a dominant influence on the dependent variable.Â Keywords:city branding and the decision of return visit